Reform and equity in the access to and use of health services in bogotá, colombia (2001)
In the present study we intended to evaluate the impact of the transformation of the national health system into the Social Security Health System upon the equity in access to health services as well as their use and quality. We interpreted equity as the equal opportunity for all people of gaining real access to health services. A cross-sectional study was designed to detect the differences, which might exist between affiliated and non-affiliated people, and the differences in access to and use of health services according to the nature of affiliation. A survey was carried out in 364 households comprising 1324 people aged 9 years or older, in which socio-demographic and labor aspects, affiliation to social security, nature of the affiliation (contributive or subsidized regime), use of health services, attention and expenditure in health services were studied. 297 randomly chosen patients of the outpatient clinics of hospitals of levels 1,2 and 3 were asked to answer a survey about affiliation, awareness of their rights, opportunity and quality of the health service, general satisfaction and social participation. Numerous differences, which could not be justified by necessity, cause for requesting attention, place where people demanded health services, attention received or use of health services, were found once adjustments for gender, age, housing stratum, occupation and income were made. These problems in equity relate to the design, structure and operation of the model of regulated competition.